Health-care preventive measures, logistics challenges and corporate social responsibility during the COVID-19 pandemic: break the ice - Sasmoko, .; Muhammad Saeed, Lodhi; Abdul Rashid, Abdul Aziz; Nur Fatihah, Abdullah Bandar; Rahimah, Embong; Mohd Khata, Jabor; Siti Nisrin, Mohd Anis; Khalid, Zaman (Emerald Publishing Limited, 2021)
Purpose – The study aims to analyze the role of coronavirus testing capacity to possibly reduce the case fatality ratio (CFR) in a large cross-section of countries. The study controlled health-care expenditures, logistics performance index (LPI), carbon damages, and corporate social responsibility (CSR) to understand the nature of causation between the CFR and stated factors. Design/methodology/approach – The study used a cross-sectional regression apparatus for coefficient estimates and variance decomposition analysis (VDA) for forecasting relationships between the variables over time. Findings – The results confirmed the W-shaped relationship between CFR and case-to-test ratio (CTR) in the presence of a LPI that exacerbates the CFR cases across countries. The VDA estimates suggest that carbon damages, logistics activities, and CSR are likely to influence CFR over time. Originality/value – To the best of the authors’ knowledge, the study is believed to be the first study that assesses the W-shaped relationship between the CFR and CTR in the presence of dynamic variables, which helps to formulate long-term sustainable health-care policies worldwide.